ATP1B3 may promote glioma proliferation and migration through MAPK/NF-KB signaling pathway - Yan, Qikang; Sun, Quan; Feng, Yan; Hu, Qingyun; Zhu, Jinling (Frontiers in Oncology, 2025)
ObjectiveTo investigate the function of ATPase Na+/K+ Transporting Subunit Beta 3 (ATP1B3) in gliomas and the molecular mechanisms associated with them in order to identify a novel target and approach for glioma clinical diagnosis and treatment.MethodsThe Cancer Genome Atlas (TCGA), a public tumor database, and the Chinese Glioma Genome Atlas (CGGA) were used to evaluate the differential expression of ATP1B3 in glioma cells of various grades. Its connection to patient survival and prognosis; The siRNA interference approach instantly reduced the amount of ATP1B3 expression in the glioma cell lines U87MG and U251MG. The knockdown efficiency was assessed by Western Blotting (WB) and RT-qPCR. Following ATP1B3 knockdown, the ability of glioma cells to proliferate, migrate, and invade was identified using the Transwell assay and CCK-8. The proteins that might interact with ATP1B3 were filtered out using the TCGA database and literature analysis. The WB assay was used to determine the expression level of Protein Phosphatase 1 Catalytic Subunit Alpha (PPP1CA) following ATP1B3 deletion, immunoprecipitation was used to determine the direct influence of the two proteins, and immunofluorescence was used to analyze the distribution of ATP1B3 and PPP1CA proteins in glioma cells. Cyclin D1 and vascular endothelial growth factor A(VEGFA) expression alterations following ATP1B3 deletion were identified using the WB assay. Following ATP1B3 knockdown, the WB assay was used to determine the expression levels of p-Raf1, p-MEK 1/2, p-ERK 1/2, p-IκBα, and p-P65 in the MAPK and NF-κB signaling pathway.ResultsDatabase analysis revealed a negative correlation between the patients’ prognosis and the expression level of ATP1B3, and a positive correlation with the malignant degree of the glioma. The mRNA and protein expression levels of ATP1B3 were significantly decreased after knockout, and the proliferation, migration and invasion ability of cells in knockout group were significantly lower than those in control group, with statistical difference. The immunoprecipitation results were negative, and the knockdown group’s PPP1CA expression was lower than the control group’s. Following ATP1B3 knockdown, Cyclin D1 and VEGFA protein expression levels dropped, and the effects were statistically significant. There was a statistically significant drop in the expression levels of p-Raf1, p-MEK 1/2, p-ERK 1/2, p-IκBα, and p-P65 following ATP1B3 deletion.ConclusionIn gliomas, ATP1B3 is highly expressed. Glioma cell motility, invasion, and proliferation all decline when ATP1B3 expression is lowered. The downstream protein PPP1CA is indirectly regulated by ATP1B3. By controlling the MAPK and NF-κB signaling pathways, ATP1B3 may have a role in the invasion, migration, and proliferation of glioma cells. As a result, the ATP1B3 gene might be a biological target for treatment and a possible neurotumor diagnostic.